The surgical efficiency of Kirschner wire sleeve-assisted removal of elastic intramedullary nails: a comparative study - Lin, Xue-Tang; Wang, Lin-Xiong; Chen, Xiao-Cong; Gong, Wei-Peng; Shang-Lin, Shang-Guan; Huang, Dong-Qing; Yang, Shu-Mu; Yi, Na-Ling; Tang, Long-Feng (Frontiers in Pediatrics, 2026)
BackgroundElastic intramedullary nails (ESIN) are widely used for pediatric fractures; however, their removal poses technical challenges. Currently, there are limited reports on improvements in ESIN removal techniques. This study aimed to explore the clinical efficacy of Kirschner Wire (K-wire) sleeve-assisted ESIN removal surgery and to provide new references for ESIN extraction in orthopedic surgery.MethodsThis retrospective study included 32 patients who underwent ESIN removal surgery at our hospital between October 2020 and July 2024. Patients were retrospectively assigned to two groups based on surgical method: the conventional instrument removal group and the K-wire cannula-assisted removal group. The efficacy of K-wire sleeve-assisted ESIN removal surgery was then compared with that of the traditional method.ResultsThe K-wire sleeve group (observation group, n = 17) exhibited a significantly shorter operative time (4.65 ± 1.12 vs. 11.33 ± 1.47 min/nail, p < 0.001) and significantly smaller incisions (0.95 ± 0.11 vs. 1.43 ± 0.33 cm/nail, p < 0.001) when compared to traditional methodology (control group, n = 15). Among the 32 patients, no cases of postoperative incision infection, intraoperative nerve injury, or vascular injury were observed.ConclusionThe Kirschner Wire (K-wire) sleeve-assisted ESIN removal technique provided a minimally invasive and cost-effective alternative to traditional methods.